Constitutional Authority Based on the Constitutional Court Decision in Indonesia - Iskandar Muda; Bintan R. Saragih; Ferry Edwar (Universitas Lampung, 2023)
At least there has been a development regarding the constitutional authority of the Constitutional Court in four ways based on its decision. It is also true that the Constitutional Court's decision is final and binding, but not in the sense of not being examined further. This study uses normative research methods. The results revealed four developments in the constitutional authority of the Constitutional Court in three ways: passive, active, and passive-active methods. Furthermore, it was also revealed; that there are also development efforts that have occurred more than once in the same matter. Therefore, in the future when the Constitutional Court decides on cases related to its authority, ideally by observing the limiting signs of the previous decision and considering the three basic characteristics of constitutional interpretation. Likewise, in the future there is another development regarding the constitutional authority of the Constitutional Court. In that case, it is appropriate to also pay attention to the three basic characteristics of constitutional interpretation.